2017
DOI: 10.1155/2017/8134321
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effect of Caulophyllum robustum on Collagen‐Induced Arthritis and Regulation of Nitric Oxide, NF‐κB, and Proinflammatory Cytokines In Vivo and In Vitro

Abstract: Caulophyllum robustum Maxim (C. robustum) has commonly been used as traditional Chinese medicine for the treatment of rheumatic pain and rheumatoid arthritis (RA) in China. This paper first investigated the anti-inflammation effect of C. robustum extraction (CRME) on RAW264.7 cells stimulated by lipopolysaccharide (LPS) and gene expression levels of inflammatory factors. Moreover, we first evaluated the anti-RA effects of CRME using collagen-induced arthritis (CIA) in DBA/1J mice, and the incidence, clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Rheumatoid arthritis affects the function of joints and tissues, which may lead to various pathological symptoms, including fatigue, general discomfort and body weight loss (34). A previous study has demonstrated that NF-κB and various pro-inflammatory cytokines are involved in the inflammation of the joints through multiple signaling pathways both in vivo and in vitro (35). In the present study, the role of the pro-inflammatory cytokine IL-1β was investigated in vitro , using sfd-FLSs, and in vivo , using a rat model of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis affects the function of joints and tissues, which may lead to various pathological symptoms, including fatigue, general discomfort and body weight loss (34). A previous study has demonstrated that NF-κB and various pro-inflammatory cytokines are involved in the inflammation of the joints through multiple signaling pathways both in vivo and in vitro (35). In the present study, the role of the pro-inflammatory cytokine IL-1β was investigated in vitro , using sfd-FLSs, and in vivo , using a rat model of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…From day 24, the thickness of the hind paws of mice was measured with Vernier calipers every 4 days. The inflammatory scores of all four paws were assessed using the following methods: 0 = normal; 1 = erythema or slight swelling in the ankle joints; 2 = erythema and slight swelling from the ankle joints-to-the toe or metacarpal joints; 3 = erythema and moderate swelling from the ankle joints-to-the toe or metacarpal joints; and 4 = erythema and severe swelling from the ankle joints-to-the toe or metacarpal joints (18). The score for each mouse was the sum of four paws; the minimum score was 0, and the maximum score was 16.…”
Section: Paw Thickness Measurement and Arthritic Index Scoringmentioning
confidence: 99%
“…It is widely believed that TNF-a plays an important role in the pathogenesis of inflammatory arthritis (15). The collagen-induced arthritis (CIA) mouse model and the collagen antibody-induced arthritis (CAIA) mouse model are often used in RA research (16,17), and macrophages can be investigated in these models (18,19).…”
mentioning
confidence: 99%